Whole-Exome Sequencing in Czech Patients with Neurogenetic Diseases - Staněk, David; Sedláčková, Lucie; Seeman, Pavel; Šafka Brožková, Dana; Laššuthová, Petra (Genetic testing and molecular biomarkers, 2020)
Aims: Genomic studies play a major role in variant observations between and within populations and in identifying causal relationships between genotypes and phenotypes. Analyses using databases such as gnomAD can provide insight into the frequencies of alleles in large populations. There have been reports that detail such frequencies for several countries and ethnic groups, but as yet, there are no such datasets for the Czech population. Patients and Methods: Whole-exome sequencing (WES) data from 222 individuals from the Czech Republic were analyzed by The Genome Analysis Toolkit best practices pipeline. These data were annotated with the ANNOVAR tool, and the allele frequencies were computed. Results: We developed a database that contains 300,111 variants in 17,512 genes. It is accessible through a simple web query available at prot2hg.com/variantbrowser. Gene-based analyses identified those genes that are most tolerant to variants in our population. Second, allele frequencies in our population were compared to the gnomAD database and groups of variants frequent in our population, but ultra-rare in gnomAD as a whole were identified. Conclusion: This tool should be useful for detecting local variants in the Czech population of patients with neurogenetic diseases.
Keywords: Female; vysoce účinné nukleotidové sekvenování; nemoci nervového systému; databáze genetické; genetická variace; genomika; Sequence Analysis, DNA; mužské pohlaví; Genetic Variation; sekvenování exomu; Databases, Genetic; Humans; alely; dospělí; frekvence genu; Neurodegenerative Diseases; Gene Frequency; Phenotype; High-Throughput Nucleotide Sequencing; Czech Republic; sekvenční analýza DNA; Alleles; lidé; fenotyp; ženské pohlaví; neurodegenerativní nemoci; genotyp; Česká republika; Nervous System Diseases; Adult; Exome Sequencing; Male; Genotype; Genomics